Mind-Body Synergy: Yoga’s Role in the Treatment and Prevention of Eating Disorders - Karthik, Vadde Venkata; Shetty, Shivaprasad; Shetty, Prashanth (Indian Journal of Integrative Medicine, 2025)
Background: One of the most prevalent psychological and psychosomatic disorders that negatively impacts mental and physical health as well as quality of life, is eating disorder. A severe chaotic eating pattern, such as that of anorexia nervosa or bulimia nervosa, is indicative of an eating disorder. Clinical scientists have long been interested in alternative medicine, and using practices like yoga to treat eating disorders has been suggested as a novel therapy strategy. In essence, yoga is about being connected and ongoing. Yoga can help individuals having trouble eating and feeding themselves reach their therapeutic goals by using mind- and body-based strategies. Methods: The data for the present review study were collected through a search of electronic resources and databases and a manual search of library resources. Relevant articles and studies were searched online on Pub Med, Google Scholar, and Science Direct using keywords such as ‘yoga’, ‘feeding and eating disorder’, ‘pranayama’, ‘relaxation’, and ‘meditation’. This study will address the potential role of yoga in treating and preventing eating disorders. Results: The findings demonstrated that emotional problems, stress, and other essentially subjective elements are the root causes of eating disorders. Yoga helps many people find harmony and relaxation in their bodies, souls, and minds. This method makes fighting eating problems more feasible. Conclusion: Yoga boosts one’s self-esteem and good body and attractiveness perception. Yoga treats people as a whole and offers a variety of ongoing, basic approaches for human health, development, preparedness, and balance. As a result, it is useful in treating eating disorders and poor nutrition.